2019
DOI: 10.1111/jfb.14117
|View full text |Cite
|
Sign up to set email alerts
|

Plectorhinchus macrolepis (Actinopterygii: Haemulidae) in the western Atlantic Ocean

Abstract: Morphometric measurements, meristic counts and DNA barcoding identified the presence of a biglip grunt Plectorhinchus macrolepis in the western Atlantic Ocean. As the species is endemic to the tropical eastern Atlantic Ocean and has not previously been reported in the western Atlantic Ocean, we discuss the possible means by which it might have dispersed to the western Atlantic Ocean. Even though this species is not considered established in Paranaguá Bay, we advocate monitoring of possible new individuals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In some invertebrate groups such as Polychaeta, with more than 10,000 species described, a total of 65 barcoding studies have been published prior to 2020. Copepoda, which are some of the most abundant organisms in our planet [39], encompassing 14,300 species (World Association of Copepoda; @copepodology), have been targeted by only 87 studies so far, with eight and ten in 2019 and 2020, respectively (Figure 1C), despite the seminal study from Bucklin et al comparing DNA barcodes to the Rosetta stone of marine biodiversity [40]. This trend likely arises from an assortment of shortcomings hindering the development of DNA barcode as a routine survey tool for several groups.…”
Section: Progress In Aquatic Dna Barcoding Studiesmentioning
confidence: 99%
“…In some invertebrate groups such as Polychaeta, with more than 10,000 species described, a total of 65 barcoding studies have been published prior to 2020. Copepoda, which are some of the most abundant organisms in our planet [39], encompassing 14,300 species (World Association of Copepoda; @copepodology), have been targeted by only 87 studies so far, with eight and ten in 2019 and 2020, respectively (Figure 1C), despite the seminal study from Bucklin et al comparing DNA barcodes to the Rosetta stone of marine biodiversity [40]. This trend likely arises from an assortment of shortcomings hindering the development of DNA barcode as a routine survey tool for several groups.…”
Section: Progress In Aquatic Dna Barcoding Studiesmentioning
confidence: 99%
“…Non‐native species from different taxonomic groups have been recorded in Brazil lately, e.g ., two species of brittle star of the genus Ophiothela (Derviche et al ., 2020; Gomes & Silva, 2020), bivalve species (Gomes & Silva, 2020) and jellyfish (Thé et al ., 2021). Non‐native teleosts have also been found along the Brazilian coast, such as Omobranchus punctatus (Valenciennes, 1836;Blenniidae) (Gerhardinger et al ., 2006), Pterois volitans (Linnaeus, 1758; Scorpaenidae) (Ferreira et al ., 2015), Plectorhinchus macrolepis (Linnaeus, 1758; Haemulidae) belonging to family (Adelir‐Alves et al ., 2019) and Pomacanthus maculosus (Forsskål, 1775; Pomacanthidae) (Soeth et al ., 2018). Taxonomic reviews have confirmed the presence of species Opsanus beta (Goode and Bean, 1880) in Brazilian coastal waters (Caires et al ., 2007) since 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the number of marine bioinvasions of several taxa has increased (Ferreira et al 2009, 2015, Bumbeer & Rocha 2016, Miranda et al 2018, and among these, invasive non-native marine fish increased in the last two decades (Gerhardinger et al 2006, Lasso-Alcalá et al 2011, Tomás et al 2012, Contente et al 2015, Ferreira et al 2015, Côa et al 2017, Soeth et al 2018, Adelir-Alves et al 2019. For example, Opsanus beta, an endemic species of the Gulf of Mexico, was first observed on the southwestern Atlantic coast in the 2000s (Caires et al 2007).…”
Section: Introductionmentioning
confidence: 99%